Vrednote, vrednosti in razvojni potenciali območij varovanja - Lampič, Barbara (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2008)
Recognition of protected areas and their valuables well as the appropriate definition of values in these areas can importantly contribute to sustainable regional development. From the development point of view the protected areas incorporate environmental, cultural, social and human potentials which, according to the protection mode, have certain direct and/or indirect applied value as well as the value of "unused". Protected areas should be understood not only as areas of protection but also as areas of great and in Slovenia not yet recognized and poorly used potentials.
Keywords: ecology; ekologija; varstvo okolja; varstvo narave; environmental protection; varstvena območja; sonaravni razvoj; sustainable development; trajnostni razvoj; strategija; vrednote; Slovenia; Slovenija